Access to health and quality of life in the rural area (Research, Society and Development, 2022)
Objective: To analyze access to health and quality of life in rural areas. Method: Integrative review, which used PubMed, LILACS, Scielo and BVS as research source. Publications from 2010 to 2020 were selected. After analysis, 23 studies were selected. Results: Most studies were from the year 2020 and 2018, these addressed the difficulty of accessing health services in rural areas. There was a lack of vacancies and professionals to meet the health demands, in addition to socioeconomic issues that affect the demand for preventive services. Conclusion: Despite the improvements achieved, mainly due to the decentralization of health, there is still a lot to be done to bring equitable health to rural areas. Since, in addition to the organizational difficulties of health services, there are socioeconomic adversities that are intrinsic to the population, which go beyond the scope of the health sector, and lack interventions from other sectors and social segments.